Feeding Ecology of the Sandbar Shark in South Carolina Estuaries Revealed through δ13C and δ15N Stable Isotope Analysis. Issue 1 (22nd July 2014) - Shiffman, David S.; Frazier, Bryan S.; Kucklick, John R.; Abel, Daniel; Brandes, Jay; Sancho, Gorka
Abstract: Stable isotope ratios of carbon and nitrogen (δ 13 C and δ 15 N) from muscle samples were used to examine the feeding ecology of a heavily exploited shark species, the Sandbar Shark Carcharhinus plumbeus . Two hundred and sixty two Sandbar Sharks were sampled in five South Carolina estuaries. There were no significant differences in average δ 13 C or δ 15 N signatures between estuaries, between sampling years, or between male and female Sandbar Sharks, suggesting that these variables do not affect diet. A potential ontogenetic diet shift between young‐of‐year and juvenile Sandbar Sharks in South Carolina, similar to a shift previously described in Virginia and Hawaii populations, is suggested by significant differences in average δ 13 C and average δ 15 N signatures between these age‐classes. Results confirm that Sandbar Sharks in South Carolina are generalist predators and that juvenile Sandbar Sharks have a wider diet breadth than young‐of‐year sharks, a pattern common in elasmobranchs. Sandbar Shark diet in South Carolina is similar to that found in previous stomach content analysis studies. This study also demonstrates that nonlethal sampling methods can be applied to sharks to obtain diet and trophic information, including the detection of ontogenetic shifts in diet. Received September 17, 2013; accepted April 1, 2014